Information need in metaverse recordings - A field study - Steinert, Patrick; Mischkies, Jan; Wagenpfeil, Stefan; Frommholz, Ingo; Hemmje, Matthias (Information Research an international electronic journal, 2026)
Introduction. Metaverse Recordings (MVRs) represent an emerging and underexplored media type within the field of Multimedia Information Retrieval (MMIR). This paper presents findings from a field study aimed at understanding the user information needs and search behaviours specific to MVR retrieval. Method. By conducting and analysing expert interviews, the study identifies application scenarios and retrieval challenges. from an MVR collection. Analysis. The collected responses were analysed to reveal patterns in user needs and behaviours. Key focus areas included interest in time-series data generated during graphical rendering and data from related input-output devices, identified as crucial components for MVR retrieval. Results. The findings outline existing application scenarios for MVRs, validate the need to capture specific data types in MVR retrieval, and emphasise the importance of user-tailored MVR retrieval systems. The study also identifies use cases, and requirements essential for the design of effective MVR retrieval systems. Conclusions. This research contributes to a foundational understanding of MVR retrieval and supports future efforts in system design and research within MMIR, enhancing the comprehension of information search behaviours in the context of the emerging multimedia type MVR.